2015
DOI: 10.1103/physreve.91.012822
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage effects of awareness cascade on epidemic spreading in multiplex networks

Abstract: Human awareness plays an important role in the spread of infectious diseases and the control of propagation patterns. The dynamic process with human awareness is called awareness cascade, during which individuals exhibit herd-like behavior because they are making decisions based on the actions of other individuals [Borge-Holthoefer et al., J. Complex Networks 1, 3 (2013)]. In this paper, to investigate the epidemic spreading with awareness cascade, we propose a local awareness controlled contagion spreading mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(92 citation statements)
references
References 37 publications
3
85
0
1
Order By: Relevance
“…[110] disappear. Furthermore, the social dynamics are further extended to an awareness cascade model [112], during which agents exhibit herd-like behavior because they make decisions referring to the actions of other individuals. Interestingly, it is found that a local awareness ratio (of unaware individuals becoming aware ones) approximating 0.5 has a two-stage effect on the epidemic threshold (i.e., an abrupt transition of epidemic threshold) and can cause different epidemic sizes, irrespective of the network structure.…”
Section: Dynamics In Multilayer Networkmentioning
confidence: 99%
“…[110] disappear. Furthermore, the social dynamics are further extended to an awareness cascade model [112], during which agents exhibit herd-like behavior because they make decisions referring to the actions of other individuals. Interestingly, it is found that a local awareness ratio (of unaware individuals becoming aware ones) approximating 0.5 has a two-stage effect on the epidemic threshold (i.e., an abrupt transition of epidemic threshold) and can cause different epidemic sizes, irrespective of the network structure.…”
Section: Dynamics In Multilayer Networkmentioning
confidence: 99%
“…Networks modeling plays a key role in identifying structural properties and analyzing the epidemic spreading on networks [1][2][3][4][5][6][7]. Meantime, it has been acknowledged for decades that connectivity patterns is an important factor in determining the properties of dynamic process [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the crisis awareness introduced into the adaptive behavior could cause a large range of shocks in the infected rate and the network topology [6]. The related studies also found that the adaptive behavioral response will make the effect of the target immune more obvious [7], and the community structure causing in the evolution of the adaptive process makes the disease controlling time more important [8,9]. The above researches focus on the dynamic characteristics in the steady state, however, the exploration of the transient characteristics is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the spread of diseases results in elevated crisis awareness and thus facilitates the diffusion of the awareness about the disease [6], but the diffusion of the awareness promotes more people to take preventive measures and consequently suppresses the epidemic spreading [4]. To understanding how awareness diffusion can mitigate epidemic outbreaks, and more broadly, the asymmetric interacting spreading dynamics led to a new direction of research in complex network science [7][8][9][10][11][12][13][14]. A pioneering step in this direction was taken by Clara [7] who studied the epidemic spreading in the multiplex networks by establishing two layers network, in which one represents epidemic spreading and another represents the diffusion of the information awareness.…”
Section: Introductionmentioning
confidence: 99%